The Study of Molecular Docking and Molecular Dynamics Simulation Chemical Compound of Pycnarrhena cauliflora Diels. as Proapoptosis in Cervical Cancer - Aini, Anggun Qurrota; Supandi, Supandi; Adelina, Rosa; Maharani, Dila Aulia (Indonesian Journal of Cancer Chemoprevention, 2024)
Cervical cancer is one of the most common cancers among women worldwide and in Indonesia. B-cell lymphoma 2 (Bcl-2) can play a role in causing cancer by inhibiting apoptosis. The purpose of this study was to analyze the chemical compound of the sengkubak plant (Pycnarrhena cauliflora Diels.), which can act as antiapoptotic inhibitor by binding to the B-cell lymphoma 2 (Bcl-2) receptor. The research was conducted in silico with molecular docking methods and molecular dynamics simulations. Molecular docking used the AutoDock 4.2.6 software and visualization used Biovia Discovery Studio. Molecular dynamics simulation used Gromacs 5.1.2 software and result visualization used Grace. Longipinocarvone was the best test ligand with the smallest ΔGbind value of -6.99 kcal/mol compared to the positive control of Doxorubicin and other compounds which indicating Longipinocarvone’s affinity for binding to the Bcl-2 receptor was better than Doxorubicin. The types of interactions involved in the molecular docking of the chemical compounds of the sengkubak plant and Doxorubicin including hydrogen bonds and hydrophobic interactions. The stability of the bond between the ligand protein complex resulting from molecular docking was analyzed based on the parameters RMSD, RMSF, Radius of Gyration (Rg) values through molecular dynamics simulations. The results of the analysis showed that Longipinocarvone and Doxorubicin had a stable bond with Bcl-2 as indicated by the RMSD and RMSF values meeting the requirements, namely <3 Å (0.3 nm). The Rg graph showed both complexes are stable during simulation and have resemblant ligand-protein movements.Keywords: Cervical cancer, B-cell lymphoma 2 (Bcl-2), Pycnarrhena cauliflora Diels., molecular docking, molecular dynamics.